Analisis Penggunaan Camshaft Berdurasi Tinggi pada Engine 2P2 - Ridwan Adam M. Noor; Fani Aditya (Universitas Negeri Makassar, 2017)
Research Target that is to know influence camshaft duration to volumetric efficiency at four stroke otto engine 130 cc. Research uses engine 2P2 with two types camshaft high duration and low duration conducted above engine dynamometer. Calculation is conducted after got data of testing result. Base testing and calculatuion can be concluded that engine that use camshaft high duration have efficiency larger ones volumetric until its power bigger. Keywords : Camshaft, Duration and power